Noncoding RNAs: biology and applications—a Keystone Symposia report. Issue 1 (17th November 2021) - Cable, Jennifer; Heard, Edith; Hirose, Tetsuro; Prasanth, Kannanganattu V.; Chen, Ling‐Ling; Henninger, Jonathan E.; Quinodoz, Sofia A.; Spector, David L.; Diermeier, Sarah D.; Porman, Allison M.; Kumar, Dhiraj; Feinberg, Mark W.; et al.
Abstract: The human transcriptome contains many types of noncoding RNAs, which rival the number of protein‐coding species. From long noncoding RNAs (lncRNAs) that are over 200 nucleotides long to piwi‐interacting RNAs (piRNAs) of only 20 nucleotides, noncoding RNAs play important roles in regulating transcription, epigenetic modifications, translation, and cell signaling. Roles for noncoding RNAs in disease mechanisms are also being uncovered, and several species have been identified as potential drug targets. On May 11–14, 2021, the Keystone eSymposium "Noncoding RNAs: Biology and Applications" brought together researchers working in RNA biology, structure, and technologies to accelerate both the understanding of RNA basic biology and the translation of those findings into clinical applications. Abstract : Noncoding RNA comprise a diverse range of RNAs. Long noncoding RNAs (lncRNA) contain features of mRNAs; the most well‐studied localize to the nucleus, help form nuclear condensates, and affect transcription machinery. Short noncoding RNA species play roles in mRNA translation, alternative splicing, and RNA editing and silencing. As new technologies are developed, the prevalence and importance of the diverse array of small RNAs will come to light. On Demand : https://keysym.us/21EK44NYAS .